1983
DOI: 10.1007/bf01121948
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a procollagenase by low-molecular-weight angiogenesis factor

Abstract: Avascular tumours have the ability to establish a blood supply for themselves by secreting a humoral factor which stimulates their host's endothelial cells to proliferate and to migrate towards the tumour source. The mechanism of action of such a humoral angiogenesis factor is more than that of an endothelial-cell growth factor since it requires an oriented migration of cells towards the tumour. We report here the activation of pure skin-fibroblast procollagenase by a low-molecular-weight angiogenesis factor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Analysis of the degradation products from the Gore-cat~ysed hydrolysis of Type-I collagen by SDS-polyacrylamide gel electrophoresis revealed the $95 and 3/o collagen fragments ~h~a~teristic of the action of mammalian collagenase 181. We have previously reported that ESAF activates a skin fibroblast procollagenase [3]. Here we have shown that heparin potentiates the action of limiting amounts of ESAF.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Analysis of the degradation products from the Gore-cat~ysed hydrolysis of Type-I collagen by SDS-polyacrylamide gel electrophoresis revealed the $95 and 3/o collagen fragments ~h~a~teristic of the action of mammalian collagenase 181. We have previously reported that ESAF activates a skin fibroblast procollagenase [3]. Here we have shown that heparin potentiates the action of limiting amounts of ESAF.…”
mentioning
confidence: 63%
“…We have also shown that ESAF activates skin fibroblast pr~olla~~e [3]. A unifying mechanism of action for a factor which is able to induce both endotherm cell proliferation and directional growth, which are properties of a~ogenic substances [4], is difficult to understand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ESAF activates latent collagenase (Weiss et al, 1983) by reversing the inhibition of this enzyme by tissue inhibitor of metalloproteinases (McLaughlin et al, 1991 (Table III). Samples were frozen at -20'C prior to extraction.…”
mentioning
confidence: 99%
“…Assay of angiogenic material for its ability to activate latent collagenase was performed according to the method of Weiss et al (1983). Results were expressed as 1tg collagen degraded h-I mg-' protein in the supernatant.…”
mentioning
confidence: 99%